Retesting the Influences on CO2 Emissions in China: Evidence From Dynamic ARDL Approach - Nurgazina, Zhanar; Guo, Qingbin; Ali, Uzair; Kartal, Mustafa Tevfik; Ullah, Arif; Khan, Zaid Ashiq (Frontiers in Environmental Science, 2022)
This study aims to demonstrate the impact of economic growth and energy consumption on environmental degradation in China, the top country that produced the highest carbon dioxide (CO2) emissions, by considering that environmental degradation is one of the extreme challenges that the world and China have been facing. Parallel to this aim, this study uses dynamic ARDL (DYNARDL) simulations to investigate the long-run and short-run cointegration amongst the selected parameters from 1979 to 2019. The results of the long-run and short-run simulations illustrate that 1) economic growth increases environmental degradation; 2) growth in energy consumption worsens the environmental degradation situation; 3) urbanization improves the environmental situation in the long run, whereas growth in urban population increases CO2 emissions in the short-run. The research argues that improved energy production and management should be included in economic policy planning and the government should invest more in renewable energy to prevent environmental degradation.